The Effectiveness of Narrative Exposure Therapy on Pregnancy Concerns, Schemas Coping with Stress and Interpersonal Sensitivity in Pregnant Women with Pregnancy Anxiety - Davoudi, Mandana; Pouladi Rishehri, Ali; Danesh, Esmat (Psychology of Woman Journal, 2023)
The aim of this study was to determine the effectiveness of narrative exposure therapy on pregnancy concerns, stress coping schemas and interpersonal sensitivity in pregnant women with pregnancy anxiety. The statistical population of the present study was all pregnant women with pregnancy anxiety in Shahid Beheshti Obstetrics and Gynecology Hospital in Nowshahr that their scores were one standard deviation above the mean and were willing to participate in treatment sessions. Using purposeful sampling method, a sample size of 75 people (for each group at least 25 people) was calculated and then these 50 people were randomly assigned to 25 persons (experimental group of narrative exposure therapy, 25 patients and control group 25) and Parker Interpersonal Sensitivity Questionnaire (1989), Wong & et al.'s Stress Coping Schemas (2006) and Alderdsey's Pregnancy Concerns, and Lane (2011) was distributed among them. In this study, after collecting data from the prototype, the data were entered into SPSS software version 26. The findings showed that the mean difference in the interpersonal sensitivity dimensions of subjects in the control group and the mean score of the experimental group was significant (P >0.05), the difference in the mean score in the dimensions of pregnancy concerns in the control group was >significant (P In fact, it can be said that narrative exposure therapy method was effective on the dimensions of coping with stress schemas of subjects.